Elements of geopolitics in Kazakh and Tuvan literature - Matkerimova, Raushan A.; Kaliyeva, Almira K. (The New Research of Tuva, 2025)
The article analyzes representations of artistic space (various elements of geopoetics) in Kazakhstani and Tuvan literature of the 20th — 21st centuries. The sources include literary works by Kazakhstani authors G. Belger, B. Kanapyanov, and N. Chernova, as well as Tuvan authors M. Mongush and Ch. Kuular.Kazakhstani and Tuvan writers employ spatial imagery to recreate the unique worldview of their peoples, including their perception of the steppe, mountains, sun, and other natural elements. In all the analyzed works by Kazakhstani and Tuvan authors, the steppe — serving as the dwelling place of nomads — emerges as the most significant element of geopoetics.Differences are also noted. In the essays by B. Kanapyanov and N. Chernova, geopoetic imagery exhibits a more pronounced subjective character compared to the stories by G. Belger, M. Mongush, and Ch. Kuular. G. Belger’s descriptions are confined to the space of the aul and its surroundings. The geopoetics in M. Mongush’s story is marked by a broad spatial scope, as the events unfold across various locations (Tuva and Mongolia). These different approaches to the depiction of geopoetics are explained by the diverse artistic objectives pursued by the authors.
Keywords: geopoetics; artistic space; steppe; perception of space; Tuvan literature; Kazakhstani literature; Turkic mythology